Makna Kultural pada Kepercayaan Masyarakat Jawa Terhadap Ketupat di Momen Lebaran: Kajian Antropologi Linguistik - Alvina Maghfiroh; Nurhayati Nurhayati (Balai Bahasa Provinsi Riau, 2023)
Ketupat in the Eid moment gives its own meaning for Javanese people. They have certain beliefs in interpretating ketupat, especially about philosophy and the process of making ketupat. This research aims to reveal the cultural meaning and local wisdom values from ketupat. This research uses qualitative methods that collecting the data use indepth interview. By using linguistic anthropological approach, the data of this research analyzed inductively and adjust translational- equivalent analysis methods. The research findings show 3 prohibitions, 6 beliefs, and 3 requirements about ketupat that the Javanese people still believe until now. The result of the research imply any local wisdom values, such as obligation to conserve Javanese culture, minimalist principle, and the concept of animism and dynamism that dominate these beliefs. Even though, they just admit to follow their ancestors culture without any goals to conduct an activity related to animism and dynamism which opposite Islamic thought.